Are Asian Sharīʼah-Compliant Equity Indices Predictable - Muhammad Umer Quddoos; Muhammad Shehryar; Asif Yaseen (Pakistan Journal of Islamic Research)
This study examines the informational efficiency in the weak-form of Islamic (Sharīʼah-compliant) equity indices of selected countries by testing the Martingale Difference Hypothesis and the Random Walk Hypothesis. The study applies Automatic Portmanteau Test (AQ) and Automatic Variance Ratio Test (AVR) on daily index return from 1st July 2009 to 30th June 2018. All indices appear to be informationally efficient (weak-form) as per the AQ Test, except FTSE Malaysia EMAS Sharīʼah Index and Jakarta Islamic Index. As per results of AVR Test, Islamic indices of China and Malaysia were not found weak-form of efficient. Whereas, as per the combined results of both AQ and AVR Tests, it is found that only three indices rejected the weak-form of efficiency and five indices are consistent with weak-form of efficiency. So, it can be concluded that Asian Islamic indices have the sufficient level of tendency towards the informational efficiency in weak form. Findings of this study will help the academicians, regulators, and policy-makers understand the application of market efficiency hypothesis, and its major aspects that need further investigation.